The Mechanism of the Ordinal Position Effect: Stability Across Sense Modalities and the Hands Crossed Context. (April 2019) - Wang, Qiangqiang; Nie, Tingting; Zhang, Weixia; Shi, Wendian
The ordinal position effect posits that items positioned earlier in an ordinal sequence are responded to faster with the left key than the right key, and items positioned later in an ordinal sequence are responded to faster with the right key than the left key. Although the mechanism of the ordinal position effect has been investigated in many studies, it is unclear whether the ordinal position effect can extend to the auditory modality and the hands crossed context. Therefore, the present study employed days as the order information to investigate this question. Days were visually or acoustically displayed on a screen in random order, and participants were instructed to judge whether the probe day they perceived was before or after the current day (days-relevant task) or to identify the color or voice of the probe day they perceived (days-irrelevant task). The results indicate the following: (a) The days before the current day were responded to faster with the left key than the right key, and the days after the current day were responded to faster with the right key than the left key, both when the days-relevant task and the days-irrelevant task were performed, regardless of the sense modality. (b) The ordinal position effect for judgments of days was also obtained in the auditory modality even when the hands were crossed. These results indicate that the ordinal position effect can extend to the auditory modality and the hands crossed context, similar to the spatial-numerical association of response codes effect of numbers.